INFLUENCE OF THE TYPE OF RAW MATERIAL ON THE METHODOLOGY OF RESEARCHING THE PERFORMANCE PROPERTIES OF TEXTILE MATERIALS - ISHCHUK, TETIANA; IVANISHENA, TETIANA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The paper analyzes approaches to assessing the performance characteristics of textile materials made from primary and secondary raw materials. A critical analysis of modern methods of testing and assessing such characteristics was conducted, and their significant limitations were identified, in particular in the context of adaptation to the specifics of materials of secondary origin. It is proven that traditional approaches do not take into account the structural and chemical variability of secondary raw materials, which reduces the quality of the final product. The need to develop improved, standardized assessment methods focused on the principles of circular economy and sustainable development is substantiated. An integrated approach to determining performance properties is proposed, which includes comprehensive studies using analytical methods. Special attention is paid to the study of changes in physical and mechanical characteristics during the operation and reprocessing of textile materials. Methods for assessing chemical stability, thermal stability, hygroscopicity and comfort, which are decisive for the consumer properties of products, are considered. Innovative approaches, in particular the use of nanocoatings and mathematical modeling, which increase the accuracy of predicting the operational behavior of materials, were also analyzed. Particular attention was paid to environmental aspects, as well as adherence to the principles of sustainable production. Emphasis was placed on the feasibility of creating a single database of properties of recycled materials to facilitate the unification of control methods and adaptation of regulatory and technical documentation. Additionally, the influence of the chemical structure of fibers, in particular functional groups, on the operational characteristics of textile materials was analyzed. It was established that the type of functional groups (hydroxyl, amino groups, ether, etc.) determines such properties as hygroscopicity, strength, comfort and wear resistance.